Sex, Race, Food Security, and Sugar Consumption Change Efficacy Among Low-Income Parents in an Urban Primary Care Setting. (April 2018) - Bruce, Marino A.; Thorpe, Roland J.; Beech, Bettina M.; Towns, Tangela; Odoms-Young, Angela
Abstract : The purpose of this study was to examine relationships between food security and parents' self-efficacy to reduce consumption of sugar-sweetened beverages and sugary snacks in a sample of parents in waiting rooms in community-based primary care clinics in West Tennessee. Results from logistic regression models underscore the need for nuanced analysis, as the results from the pooled regression models differ from those stratified by food security status. Self-efficacy is an important factor for behavior change, and our study highlights the need for additional research examining how social, psychological, and behavioral factors have implications for behavior change self-efficacy.